Pengaruh Jenis dan Dosisi Pupuk Bokashi Terhadap Pertumbuhan dan Hasil Kacang Panjang (Vigna sinensis L.) - Achmad Djunaedy (Agrovigor, 2009)
The purpose of this Research to determine the effect of fertilizer type and dose of bokashi of growth and yield bean (Vigna sinensis L.). Results of research: 1) bokashi fertilizer and chicken manure effect on plant length and number of leaves at the age of 24 days after the plant, 2) dose of fertilizer bokashi or chicken manure is best for the total fruit weight per plant is 20 tons / ha.